Translational, multidisciplinary and integrative studies in neurophysiology: real need or contemporary fashion in brain research - Hrnčić, Dragan (Medicinski podmladak, 2018)
Why brain research is important? Do we have strategies to cope with brain diseases? What can we do to facilitate the progress in our understanding of basic and advanced neurophysiology functions responsible for our successful integration in the environmental eco –system? These are just some of the questions that all stakeholders in big arena of brain research share in common. In order to be more understandable for policy makers and the society, neuroscience, neurological and psychiatric research are nowadays frequently referred to as brain research. In the same sense, brain diseases encompass disorders also known as neurological or psychiatric.